Selected news from the 2014 Genitourinary Cancers Symposium: translating novel strategies into clinical practice. (November 2014) - Bianconi, Maristella; Santoni, Matteo; Massari, Francesco; Faloppi, Luca; Prete, Michela Del; Giampieri, Riccardo; Ciccarese, Chiara; Modena, Alessandra; Tortora, Giampalo; Scartozzi, Mario; Cascinu, Stefano
2014 Genitourinary Cancers Symposium San Francisco, CA, USA, 30 January–1 February 2014: The American Society of Clinical Oncology symposium dedicated to genitourinary tumors represents an unmissable opportunity for the whole oncology community with a special interest in the diagnosis and treatment of genitorurinary tract malignancies, in particular kidney and prostate tumors. The 2014 Genitourinary Cancers Symposium focused attention on the need to find a personalized therapy for metastatic renal cell carcinoma and castration-resistant prostate cancer patients. The development of biomarkers for tumor response and/or resistance will represent a major step in this context and has been the focus of several researches at the symposium.